RUR - Čupová, Kateřina (Rosarium Publishing, 2024)
"The R.U.R. Factory, far from humanity on its own island, has produced the perfect product: Robots! Devoid of pain, love, and all human emotion, never tiring, never bored, unfazed by death they are the ideal worker for modern-day society! All of this is about to change, and only Helena can see it. She is condemned to remain alone in her dread, as all of society embraces the robots and the automatons' presence increases. However, there has been a glitch in the programming. All of our assumptions may have been wrong. The robots may indeed feel pain. They may harbor passions and hatred, and the Robot Revolution may be near!" -- Page [4] of cover.